Glycogen synthase activity in Candida albicans is partly controlled by the functional ortholog of Saccharomyces cerevisiae Gac1p - Jian Miao; David L. Williams; Michael D. Kruppa; Brian M. Peters (mSphere, 2024)
ABSTRACT To adapt to various host microenvironments, the human fungal pathogen Candida albicans possesses the capacity to accumulate and store glycogen as an internal carbohydrate source. In the model yeast Saccharomyces cerevisiae, ScGlc7p and ScGac1p are the serine/threonine type 1 protein phosphatase catalytic and regulatory subunits that control glycogen synthesis by altering the phosphorylation state of the glycogen synthase Gsy2p. Despite recent delineation of the glycogen synthesis pathway in C. albicans, the molecular events driving synthase activation are currently undefined. In this study, using a combination of microbiologic and genetic techniques, we determined that the protein encoded by uncharacterized gene C1_01140C, and not the currently annotated C. albicans Gac1p, is the major regulatory subunit involved in glycogen synthesis. C1_01140Cp contains a conserved GVNK motif observed across multiple starch/glycogen-binding proteins in various species, and alanine substitution of each residue in this motif significantly impaired glycogen accumulation in C. albicans. Fluorescent protein tagging and microscopy indicated that C1_01140Cp-GFPy colocalized with CaGlc7p-tdTomato and CaGsy1p-tdTomato accordingly. Co-immunoprecipitation assays further confirmed that C1_01140Cp associates with CaGlc7p and CaGsy1p during glycogen synthesis. Lastly, c1_01140cΔ/Δ exhibited colonization defects in a murine model of vulvovaginal candidiasis. Collectively, our data indicate that uncharacterized C1_01140Cp is the functional ortholog of the PPP1R subunit ScGac1p in C. albicans.IMPORTANCEThe capacity to synthesize glycogen offers microbes metabolic flexibility, including the fungal pathogen Candida albicans. In Saccharomyces cerevisiae, dephosphorylation of glycogen synthase by the ScGlc7p-containing phosphatase is a critical rate-limiting step in glycogen synthesis. Subunits, including ScGac1p, target ScGlc7p to α-1,4-glucosyl primers for efficient ScGsy2p synthase activation. However, this process in C. albicans had not been delineated. Here, we show that the C. albicans genome encodes for two homologous phosphatase-binding subunits, annotated CaGac1p and uncharacterized C1_01140Cp, both containing a GVNK motif required for polysaccharide affinity. Surprisingly, loss of CaGac1p only moderately reduced glycogen accumulation, whereas loss of C1_01140Cp ablated it. Fluorescence microscopy and co-immunoprecipitation approaches revealed that C1_01140Cp associates with CaGlc7p and CaGsy1p during glycogen synthesis. Moreover, C1_01140Cp contributed to fungal fitness at the vaginal mucosa during murine vaginitis. Therefore, this work demonstrates that glycogen synthase regulation is conserved in C. albicans and C1_01140Cp is the functional ortholog of ScGac1p.